Comparison of pelvic organ prolapse recurrence between abdominal sacrocolpopexy and vaginal uterosacral ligament suspension/sacrospinous fixation - Jrais, Dr. Arwa (Saudi Journal of Obstetrics and Gynecology, 2022)
Introduction and Hypothesis: Pelvic organ prolapse usually involves the descent of one or more of the vaginal walls and/or the uterus. Pregnancy and age are the most common causes. Although it is often asymptomatic, it has a high prevalence. Several approaches are used to fix pelvic organ prolapse, but the best procedure remains undetermined. In this study, we evaluated the primary surgical outcomes to compare the efficacy between abdominal sacrocolpopexy and vaginal uterosacral ligament suspension/sacrospinous fixation in fixing and preventing recurrence of utero-vaginal or vault prolapse. Methods: This retrospective cohort study included 110 patients who underwent either sacrocolpopexy, uterosacral ligament suspension, or sacrospinous fixation between 2016 and 2019 at King Abdulaziz Medical City and who were followed up for >1 year using pelvic organ prolapse quantification (POP-Q). Primary outcome was Recurrence rate, and secondary outcome sexual and overall satisfaction using Likert scale. All patients who met the inclusion and exclusion criteria were included. The required data were collected from medical charts, then analyzed using the chi-square test and t-test. Results were reported as frequency, percentage, mean, and standard deviation. Results: The most affected women were those aged 40-49 years with 7-9 previous deliveries; 4 th degree prolapse was the most common. The most frequent procedure was sacrocolpopexy, and the most common postoperative complication was dyspareunia. Conclusions: There were no differences in recurrence rates among the approaches. Uterosacral ligament suspension or sacrospinous fixation is more suitable for multiparous women with 2nd -degree prolapse as they resulted in fewer postsurgical complications (especially dyspareunia). Sacrocolpopexy may be preferred for patients with advanced pelvic organ prolapse, especially those aged 50-59 years. Key words: dyspareunia, pelvic organ prolapse, postoperative complications, uterine prolapse, vaginal prolapse